MODEL AGE-PERIOD-COHORT UNTUK TABEL MORTALITAS DINAMIK - MIASARY, SEFTINA DIYAH ([Yogyakarta] : Universitas Gadjah Mada, 2015)
Dynamic life tables arise from the necessity to incorporate the effect of the year of death into the estimation of the measurement of mortality. The advance in statistical tables to capture the historical evolution of mortality encourages the need to improve the adjustment method of mortality prediction. Age-period-cohort (APC) models is recommended for actuaries because it have given good result in the field of epidemiology. These models constitute an evolution of dynamic models as they incorporate the year of birth (cohort) into models with age and period effects. This research used the models suggested by Holford [1983] and Clayton dan Schifflers [1987] to adjust mortality in Spain and study the effect of the cohort in this country. Then, the prediction of mortality rates can be obtained from the estimation of APC models based on the three effects